CMET-14. BRAIN METASTASES: A NEW PATHOPHYSIOLOGY, A NEW TREATMENT PARADIGM, AND, PERHAPS, A NEW PROGNOSIS. (11th November 2019) - Dowd, Richard; Ouyang, Tao; Thamburaj, Krishnamoorthy; Aregawi, Dawit; Safran, Howard; Zacharia, Brad; Glantz, Michael
Abstract: INTRODUCTION: Brain metastases are widely held to reach the CNS through the blood stream. We provide evidence that the initial site of most CNS metastases is the CSF, with subsequent invasion of brain parenchyma. We also model the therapeutic implications of this novel hypothesis. METHODS: Two neuro-radiologists independently assessed whether brain metastases were contiguous with CSF spaces in 200 consecutive patients using pre-treatment MRI. CSF was examined for malignant cells in 66 newly diagnosed, previously untreated patients. We contoured normal brain MRIs of 3 patients to calculate the percentage of brain within 5 mm of a CSF space. We queried an international neoplastic meningitis database to document response of brain metastases to intra-CSF chemotherapy. RESULTS: Mean age was 64.2. One hundred patients were male; 143 had lung cancer, 15 melanoma, 12 gastrointestinal, 11 breast, 9 renal, 7 bladder. Mean number of metastases was 4.63. Eighty-five percent of metastases touched a CSF space. In 67% of patients, all metastases touched a CSF space. Neither histology, number or size of metastases, nor patient age predicted contiguity with CSF spaces. In our consecutive subset of patients, 44% (10/23) with one, 46% (5/11) with two, 63% (5/8) with three, and 71% (17/24) with >3 metastases had malignant cells in the CSF (R 2 =0.93, p=0.037). Five of 7 patients with both brain and CSF metastases receiving only IT chemotherapy experienced a substantial reduction in the size of at least some metastases. Up to 75% of the brain parenchyma lies within 5 mm of CSF spaces. CONCLUSIONS: Our data suggest that brain metastases may access the CNS through the CSF rather than the bloodstream. IT chemotherapy may treat brain metastases. We suggest that the CSF should be monitored in all patients with, or at risk for, brain metastases. True cures may require treatment of the CSF space.